Biostratigraphy of Gurpi Formation in Samand anticline (Lurestan province) Based on calcareous nannofossils - samira shahriyary (Journal of Stratigraphy and Sedimentology Researches, 2017)
The present study is an attempt to biostratigraphically classify the rocks of Gurpi Formation at Samand Anticline with the help of calcareous nannofossils. The succession measures 197 meters in thickness and consists of shale, marl and marly limestone. A total of 96 species belonging to 45 genera of calcareous nannofossils have been identified whose distribution points to delineation of 11 international biozones. Consequently, the rocks of Gurpi Formation are attributed to middle Campanian through late Paleocene (Selandian) time and the K/Pg boundary interval is found to be continuous. Taking into account the absence of nannofossil biozones NP2-NP4 as well as the sedimentological evidence observed, the non-deposition event at the boundary interval has occurred later than the previously thought time identified on the basis of planktic foraminifera. Consequently, the rocks of Gurpi Formation are attributed to middle Campanian through late Paleocene (Selandian) time and the K/Pg boundary interval is found to be continuous. Taking into account the absence of nannofossil biozones NP2-NP4 as well as the sedimentological evidence observed, the non-deposition event at the boundary interval has occurred later than the previously thought time identified on the basis of planktic foraminifera.